Inovirus-Encoded Peptides Induce Specific Toxicity in Pseudomonas aeruginosa - Juehua Weng; Yunxue Guo; Jiayu Gu; Ran Chen; Xiaoxue Wang (Viruses)
Pseudomonas aeruginosa is a common opportunistic pathogen associated with nosocomial infections. The primary treatment for infections typically involves antibiotics, which can lead to the emergence of multidrug-resistant strains. Therefore, there is a pressing need for safe and effective alternative methods. Phage therapy stands out as a promising approach. However, filamentous prophages (Pfs) commonly found in P. aeruginosa encode genes with phage defense activity, thereby reducing the efficacy of phage therapy. Through a genomic analysis of the Pf4 prophage, we identified a 102 bp gene co-transcribed with the upstream gene responsible for phage release (zot gene), giving rise to a 33-amino-acid polypeptide that we have named Pf4-encoded toxic polypeptide (PftP4). The overexpression of PftP4 demonstrated cellular toxicity in P. aeruginosa, with subcellular localization indicating its presence in the cell membrane and a subsequent increase in membrane permeability. Notably, PftP4 homologues are found in multiple Pf phages and exhibit specificity in their toxicity towards P. aeruginosa among the tested bacterial strains. Our study reveals that the novel Pf-encoded polypeptide PftP4 has the potential to selectively target and eradicate P. aeruginosa, offering valuable insights for combating P. aeruginosa infections.